Clinical and epidemiological profiles of individuals with drug-resistant tuberculosis - Paro Pedro, Heloisa da Silveira [UNESP]; Tonelli Nardi, Susilene Maria; Ferreira Pereira, Maria Izabel; Oliveira, Rosangela Siqueira; Suffys, Philip Noel; Gomes, Harrison Magdinier; Finardi, Amanda Juliane; Moraes, Eloise Brasil de; Foschiani Dias Baptista, Ida Maria; Dantas Machado, Ricardo Luiz [UNESP]; Castiglioni, Lilian [UNESP] (Fundaco Oswaldo Cruz, 2015)
Drug-resistant tuberculosis (TB) is a growing global threat. Approximately 450,000 people developed multidrugresistant TB worldwide in 2012 and an estimated 170,000 people died from the disease. This paper describes the sociodemographic, clinical-epidemiological and bacteriological aspects of TB and correlates these features with the distribution of anti-TB drug resistance. Mycobacterium tuberculosis (MT) cultures and drug susceptibility testing were performed according to the BACTEC MGIT 960 method. The results demonstrated that MT strains from individuals who received treatment for TB and people who were infected with human immunodeficiency virus were more resistant to TB drugs compared to other individuals (p < 0.05). Approximately half of the individuals received supervised treatment, but most drug-resistant cases were positive for pulmonary TB and exhibited positive acid-fast bacilli smears, which are complicating factors for TB control programs. Primary healthcare is the ideal level for early disease detection, but tertiary healthcare is the most common entry point for patients into the system. These factors require special attention from healthcare managers and professionals to effectively control and monitor the spread of TB drug-resistant cases.
Keywords: Tuberculosis; Diagnosis; Antimicrobial resistance